Teacher's Understanding of Project Learning Models through Children's Comics with STEAM Content in Indonesia - Hapidin; Yuli Pujianti; Erie Siti Syarah; Winda Gunarti (Jurnal Pendidikan Usia Dini, 2023)
Comic media is one of the learning media that can contain messages and information about various knowledge, experiences, and events in a complete, interesting, and meaningful way. The contents of these stories can also accommodate a variety of learning content such as science, technology, engineering, art, and mathematics known as STEAM content (Science, Technology, Engineering, Art, and Math). This study aims to obtain information on teachers' understanding of the project learning model and STEAM content used in ECE units. Based on survey research and case studies, this research involved 34 ECE teacher participants representing teachers in the Seribu Islands district, DKI Jakarta. Data collection was carried out using a Google form questionnaire, participatory observation, focused discussions, and document analysis. The research produced several findings, first, comic media is very effective and interesting to provide an overview of STEAM project activities and content for ECE units. Second, learning projects containing STEAM content can be designed through learning tools and teaching modules based on maritime themes. Third, project learning with STEAM content can be one of the characteristics of the implementation of the independent curriculum in ECE units. Finally, the use of comic media in project learning with STEAM content can increase early childhood maritime cultural literacy. It is hoped that the use of comic media will help ECE educators in the Seribu Islands Regency improve their understanding of maritime cultural literacy in early childhood. Keywords: teacher's understanding, ECE steam content, children's comics References: Almulla, M. A. (2020). The Effectiveness of the Project-Based Learning (PBL) Approach as a Way to Engage Students in Learning. SAGE Open, 10(3). https://doi.org/10.1177/2158244020938702 Asghar, A., Ellington, R., Rice, E., Johnson, F., & Prime, G. M. (2012). Supporting STEM Education in Secondary Science Contexts. Interdisciplinary Journal of Problem-Based Learning, 6(2). https://doi.org/10.7771/1541-5015.1349 Bagiati, A., & Evangelou, D. (2015). Engineering curriculum in the preschool classroom: The teacher’s experience. European Early Childhood Education Research Journal, 23(1), 112–128. https://doi.org/10.1080/1350293X.2014.991099 Brown, R., Brown, J., Reardon, K., & Merrill, C. (2011). Understanding STEM: Current Perceptions. Technology and Engineering Teacher. Chen, Y.-L., Huang, L.-F., & Wu, P.-C. (2021). Preservice Preschool Teachers’ Self-efficacy in and Need for STEM Education Professional Development: STEM Pedagogical Belief as a Mediator. Early Childhood Education Journal, 49(2), 137–147. https://doi.org/10.1007/s10643-020-01055-3 Connor, A. M., Karmokar, S., & Whittington, C. (2015). From STEM to STEAM: Strategies for Enhancing Engineering & Technology Education. International Journal of Engineering Pedagogy (IJEP), 5(2), 37. https://doi.org/10.3991/ijep.v5i2.4458 DeJarnette, N. K. (2018). Implementing STEAM in the Early Childhood Classroom. European Journal of STEM Education, 3(3), 1–9. https://doi.org/10.20897/ejsteme/3878 EL-Deghaidy, H., Mansour, N., Alzaghibi, M., & Alhammad, K. (2017). Context of STEM Integration in Schools: Views from In-service Science Teachers. EURASIA Journal of Mathematics, Science and Technology Education, 13(6). https://doi.org/10.12973/eurasia.2017.01235a Farida, N., & Rasyid, H. (2019). The Effectiveness of Project-based Learning Approach to Social Development of Early Childhood. 296(Icsie 2018), 369–372. https://doi.org/10.2991/icsie-18.2019.67 Garba, S. A., Byabazaire, Y., & Busthami, A. H. (2015). Toward the use of 21stcentury teaching-learning approaches: The trend of development in Malaysian schools within the context of Asia Pacific. International Journal of Emerging Technologies in Learning, 10(4), 72–79. https://doi.org/10.3991/ijet.v10i4.4717 Gartrell, D. (2016). Developmentally Appropriate STEM: It’s STREAM! www.ChildCareExchange.com Gebbie, D. H., Ceglowski, D., Taylor, L. K., & Miels, J. (2012). The Role of Teacher Efficacy in Strengthening Classroom Support for Preschool Children with Disabilities Who Exhibit Challenging Behaviors. Early Childhood Education Journal, 40(1), 35–46. https://doi.org/10.1007/s10643-011-0486-5 Hapidin, ., Dhieni, N., & Pujianti, Y. (2020). Transformative Education Perspective: The Maritime Cultural Literacy of the Society Kepulauan Seribu, Dki Jakarta, Indonesia. 168–174. https://doi.org/10.5220/0008996001680174 Hapidin, Nurjannah, & Hartati, S. (2018). Pengembangan Model Pembelajaran Tematik Integratif berbasis proyek dalam menerapkan pendidikan kelautan pada anak di Kepulauan Seribu. Jurnal Pendidikan Usia Dini, 12(1), 51–65. https://doi.org/10.21009/JPUD.121 Hapidin, Nurjannah, S. H. (Universitas N. J. (2018). PENGEMBANGAN MODEL PEMBELAJARAN TEMATIK SERIBU. Pendidikan Usia Dini, 12(Marine Education), 51–65. https://doi.org/10.21009/JPUD.121 Herro, D., & Quigley, C. (2017). Exploring teachers’ perceptions of STEAM teaching through professional development: Implications for teacher educators. Professional Development in Education, 43(3), 416–438. https://doi.org/10.1080/19415257.2016.1205507 Horrace, R. (2021). STREAM into Online Play Groups How Children Adapt to Play in a Rapidly Digitized World. International Journal of the Whole Child, 6(1). https://libjournals.mtsu.edu/index.php/ijwc/article/view/2048 Ismuwardani, Z., Nuryatin, A., & Doyin, M. (2018). Implementation of Project Based Learning Model to Increased Creativity and Self-Reliance of Students on Poetry Writing Skills. Journal of Primary Education, 8(1), 51–58. https://doi.org/10.15294/jpe.v8i1.25229 Jamil, F. M., Linder, S. M., & Stegelin, D. A. (2018). Early Childhood Teacher Beliefs About STEAM Education After a Professional Development Conference. Early Childhood Education Journal, 46(4), 409–417. https://doi.org/10.1007/s10643-017-0875-5 Kim, H., Sefcik, J. S., & Bradway, C. (2017). Characteristics of Qualitative Descriptive Studies: A Systematic Review. Research in Nursing & Health, 40(1), 23–42. https://doi.org/10.1002/nur.21768 Lampe, M. (2012). Bugis–Makassar seamanship and reproduction of maritime cultural values in Indonesia. Jurnal Humaniora, 24(2), 121–132. Maiorca, C., Roberts, T., Jackson, C., Bush, S., Delaney, A., Mohr-Schroeder, M. J., & Soledad, S. Y. (2021). Informal Learning Environments and Impact on Interest in STEM Careers. International Journal of Science and Mathematics Education, 19(1), 45–64. https://doi.org/10.1007/s10763-019-10038-9 Margot, K. C., & Kettler, T. (2019). Teachers’ perception of STEM integration and education: A systematic literature review. International Journal of STEM Education, 6(1), 2. https://doi.org/10.1186/s40594-018-0151-2 Mengmeng, Z., Xiantong, Y., & Xinghua, W. (2019). Construction of STEAM Curriculum Model and Case Design in Kindergarten. American Journal of Educational Research, 7(7), 485–490. https://doi.org/10.12691/education-7-7-8 Prameswari, T., & Anik Lestariningrum. (2020). Strategi Pembelajaran Berbasis STEAM Dengan Bermain Loose Parts Untuk Pencapaian Keterampilan 4c Pada Anak Usia 4-5 Tahun. Efektor, 7(1), 24–34. https://doi.org/10.29407/e.v7i2.14387 Quigley, C. F., Herro, D., & Jamil, F. M. (2017). Developing a Conceptual Model of STEAM Teaching Practices. School Science and Mathematics, 117(1–2), 1–12. https://doi.org/10.1111/ssm.12201 Relevansi, U. D. A. N., & Ahmad, T. A. (2017). Urgensi Dan Relevansi Pembelajaran Sejarah Maritim Untuk Wilayah Pedalaman. Paramita: Historical Studies Journal, 27(1), 113–126. https://doi.org/10.15294/paramita.v27i1.9190 Sharapan, H. B. (2012). From STEM to STEAM: How Early Childhood Educators Can Apply Fred Rogers’ Approach. Young Children, 67, 36–40. Shernoff, D. J., Sinha, S., Bressler, D. M., & Ginsburg, L. (2017). Assessing teacher education and professional development needs for the implementation of integrated approaches to STEM education. International Journal of STEM Education, 4(1), 13. https://doi.org/10.1186/s40594-017-0068-1 Simoncini, K., & Lasen, M. (2018). Ideas About STEM Among Australian Early Childhood Professionals: How Important is STEM in Early Childhood Education? International Journal of Early Childhood, 50(3), 353–369. https://doi.org/10.1007/s13158-018-0229-5 Smith, K. L., Rayfield, J., & McKim, B. R. (2015). Effective Practices in STEM Integration: Describing Teacher Perceptions and Instructional Method Use. Journal of Agricultural Education, 56(4), 182–201. https://doi.org/10.5032/jae.2015.04183 Srikoom, W., Hanuscin, D. L., & Faikhamta, C. (2017). Perceptions of in-service teachers toward teaching STEM in Thailand. Asia-Pacific Forum on Science Learning and Teaching, 18(2). Wahyuningsih, S., Nurjanah, N. E., Rasmani, U. E. E., Hafidah, R., Pudyaningtyas, A. R., & Syamsuddin, M. M. (2020). STEAM Learning in Early Childhood Education: A Literature Review. International Journal of Pedagogy and Teacher Education, 4(1), 33. https://doi.org/10.20961/ijpte.v4i1.39855